2003
DOI: 10.1359/jbmr.2003.18.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Cadmium Exposure on Forearm Bone Density

Abstract: Cadmium may have both direct and indirect effects on bone turnover. It is nephrotoxic and can interfere with vitamin D metabolism. Such perturbation may result in osteoporosis and osteomalacia. In this study, a total of 790 persons (302 males and 488 females) participated; they were all over 35 years old and resided in an area near a cadmium smelter in southeast China. All participants completed a questionnaire, and bone mineral density was measured by SPA-4 single-photon absorptiometry at the radius and ulna.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 12 publications
(17 reference statements)
5
57
1
2
Order By: Relevance
“…(3)(4)(5)(6) It should be noted, however, that our results indicate an increased risk of osteoporosis at considerably lower Cd exposures. In addition, the results for BMD at the lumbar spine may indicate a greater public health concern than recognized previously.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…(3)(4)(5)(6) It should be noted, however, that our results indicate an increased risk of osteoporosis at considerably lower Cd exposures. In addition, the results for BMD at the lumbar spine may indicate a greater public health concern than recognized previously.…”
Section: Discussioncontrasting
confidence: 65%
“…This severe disease was characterized by renal and bone damage, with bone deformities and multiple fractures occurring as a consequence. (2) Recently, Cd has been associated with low bone mass of the forearm (3)(4)(5)(6) and the hip (7) at considerably lower exposure levels in some but far from all studies. (8)(9)(10)(11) Therefore, a possible role of Cd in the public health context of osteoporosis needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical features associated with osteoporosis include increased morbidity (ie, pain, physical impairment, and decreased quality of life), increased risk of new fractures, and increased mortality. (7) Studies among populations from Belgium, (4,8) Sweden, (9)(10)(11) Japan, (12) and China (13,14) showed associations between osteoporosis and low-level environmental cadmium exposure. The generally accepted interpretation has been that cadmiuminduced renal tubular damage (2) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria (2) and low BMD and hence increased fracture risk, (4,11) particularly in postmenopausal women (4,8) or men in the older age group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increased risk of fractures was also noted in the Swedish Oscar study, demonstrating an elevated hazard ratio already at exposure levels of 2-4 lg/g creatinine . Studies in China have reported that osteoporosis is related to kidney dysfunction, especially to tubular damage and its severity (Wang et al 2003;Jin et al 2004). Although women are believed to be more susceptible than men, a study in middle-aged men (mean age 45 years) exposed to Cd in an occupational setting showed a dose-dependent increase of osteoporosis.…”
Section: Osteoporosismentioning
confidence: 99%
“…Clinical features associated with osteoporosis include increased morbidity (pain, physical impairment, decreased quality of life), increased risk of new fractures and increased mortality (Van der Klift et al 2002). Studies among populations from Belgium (Staessen et al 1999;Schutte et al 2008b), Sweden (Järup et al 1998a;Alfvén et al 2000;Å kesson et al 2006), Japan and China Jin et al 2004;Wang et al 2003) showed associations between osteoporosis and low-level environmental Cd exposure. The generally accepted interpretation has been that Cd-induced renal tubular damage (Staessen et al 1994) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria and decreased bone mineral density, and hence increased fracture risk (Järup et al 1998c;Staessen et al 1994) particularly in postmenopausal women (Schutte et al 2008b;Staessen et al 1999) or men in the older age group .…”
Section: Osteoporosismentioning
confidence: 99%